(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
This study aimed to identify rice landraces exhibiting dual tolerance to salinity and submergence using a hydroponic screening system. Thirty-day-old seedlings of 19 rice landraces and six check varieties were exposed to salinity stress (8 and 12 dS/m, imposed using crude sea salt) and complete submergence under both freshwater and saline (8 dS/m) conditions. Morphological screening, based on a composite stress tolerance score integrating germination performance, growth response, and biomass reduction, identified Kakua as the most tolerant genotype. Several landraces, including Sona joly, Nazira shail, Sylhet balam, and Bhagnoli, exhibited moderate tolerance. Genetic diversity analysis using SSR markers (RM585 and SC3) revealed distinct clusters. Landraces such as Goccha, Machranga, and Biran grouped with the tolerant check variety Binadhan 10, while Sylhet balam, Dud shail, and Kakua showed a close genetic association with Binadhan 11. By integrating morphological and molecular data, the study identifies Kakua, Sylhet balam, Dud shail, Nonia, Roa, Sona joly, Goccha, and Machranga as promising genetic resources for breeding programs aimed at improving dual tolerance to salinity and submergence in rice. Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 399-413